PENGARUH K-POP BRAND AMBASSADOR TERHADAP LOYALITAS KONSUMEN: Studi Pada Pengguna Shopee - Chairunnisa Nurul Maulida; Arina Dieni Kamila (Kinesik, 2021)
Korean culture is currently growing rapidly and expanding globally. It's existence tends to be accepted by public from various circles, resulting in a phenomenon of "Korean Wave" or also called Hallyu. This phenomenon can be found in Indonesia and its impact is felt in everyday life, especially for the millennial generation. This has led several companies such as Shopee to carry out promotional activities using the K-Pop Boy Group Brand Ambassador named Stray Kids to maintain consumers loyalty. This study aims to determine the effect of K-Pop Brand Ambassador on consumers loyalty. With quantitative research methods and explanatory research types with the aim of knowing how much influence K-Pop Brand Ambassadors have on consumer loyalty. Equipped with SR (Stimulus-Response), a theory which helps researchers in analyzing the influence of K-Pop Brand Ambassadors on consumer loyalty. The sampling technique in this study uses non-probability sampling with a total sample of 100 (one hundred) people in accordance with the criteria determined by the researcher. For data collections, this study uses a questionnaire with Likert Scale measurements, with the help of the SPSS program to assist researchers in calculating the results of the distribution of the questionnaire. The results of this study indicate that there is an influence between K-Pop Brand Ambassadors on Consumer Loyalty of 0.242 or 24,2%.